Effectiveness of Expressive Writing therapy on Emosional Handling Adolescent Girls at X Orphanage: Efektifitas terapi Expresive Writing terhadap Pengendalian Emosi pada Remaja Puteri di Panti Asuhan X - Wardah Berlian Wadjdi; Lely Ika Mariyati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Adolescence is a developmental period marked by complex emotional changes, particularly among adolescent girls living in orphanages who experience limited emotional support and environmental differences from nuclear families. Specific Background: Difficulties in emotional control among orphaned adolescent girls may manifest in withdrawal, irritability, and maladaptive behaviors, highlighting the need for structured psychological interventions. Knowledge Gap: Although expressive writing has been applied in various emotional contexts, limited empirical evidence exists regarding its application for improving emotional control among adolescent girls in orphanage settings. Aims: This study aims to examine the role of Expressive Writing Therapy (EXPRIT) in improving emotional control among adolescent girls residing in an orphanage. Results: Using a one-group pretest-posttest experimental design with four participants, statistical analysis through Paired Sample T-Test showed a significant difference between pretest (M = 9.500) and posttest scores (M = 30.500), with p = 0.032 (p < 0.05), indicating improved emotional control following intervention. Novelty: This study focuses specifically on adolescent girls in a Muhammadiyah-affiliated orphanage and integrates psychoanalytic catharsis theory with structured expressive writing sessions. Implications: Findings suggest that expressive writing therapy may serve as a structured psychological intervention to support emotional control development among vulnerable adolescents in institutional care settings. Keywords: Expressive Writing Therapy, Emotional Control, Adolescent Girls, Orphanage Setting, Psychological Intervention Key Findings Highlights: Significant score increase observed after structured writing sessions. Statistical testing confirmed measurable emotional regulation improvement. Intervention demonstrated feasibility within institutional care context.